Layered multiple description coding - Chou, Philip A.; Wang, Helen; Padmanabhan, Venkata N.; Chou, Philip A.; Padmanabhan, Venkat (Packet Video Workshop, 2003)
Multiple description codes address the problem of unreliable channels by means of independent descriptions, while layered codes address the problems of heterogeneous client bandwidths and dynamic network congestion by means of sequences of layers. With the goal of achieving both robustness to unreliable channels and adaptivity to client bandwidth heterogeneity and network congestion, we explore constructions for layered multiple description codes, where base layer descriptions can be transmitted to low bandwidth clients, while both base and enhancement layer descriptions can be transmitted to high bandwidth clients. The low bandwidth client quality is an increasing function of the number of base layer descriptions received, while the high bandwidth client quality is a bivariate increasing function of both the number of base layer descriptions and the number of enhancement-layer descriptions received. By optimizing the base layer descriptions for the low bandwidth client, in our construction, the high bandwidth client pays a penalty of 1.4 dB relative to a non-layered multiple description code optimized to the high bandwidth client.